Corneal Topographic Astigmatism Based on Total Corneal Power Data (CorT Total): A Benchmark for Total Corneal Astigmatism. Issue 4 (April 2020) - Alpins, Noel; Ong, James K. Y.; Randleman, J. Bradley; Nevyas-Wallace, Anita; Stamatelatos, George
Abstract : Purpose: To evaluate how closely manufacturer-provided measures of total corneal astigmatism correspond with the manifest refractive cylinder, as compared to a benchmark of corneal topographic astigmatism calculated on the basis of measured total corneal power (TCP) data (CorT Total). Methods: The SD of the ocular residual astigmatism magnitude (ORAsd) was evaluated for normal virgin eyes based on an optimized benchmark CorT Total and the various measures of total corneal astigmatism provided by 3 different Scheimpflug tomographers. Results: The CorT Total corresponded with the manifest refractive cylinder at least as well as all the measures of total corneal astigmatism provided by the tomographers [Sirius CorT Total ORAsd: 0.320D (standard error [SE] 0.017D), Sirius TCP 4 mm ORAsd: 0.324D (SE 0.017D); Pentacam CorT Total ORAsd: 0.338D (SE 0.027D), Pentacam total corneal refractive power apex zone 4 mm ORAsd: 0.337D (SE 0.029D); Galilei CorT Total ORAsd: 0.472D (SE 0.068D), and Galilei TCP2 ORAsd: 0.536D (SE 0.124D)]. The difference between CorT Total and best measure on each tomographer was not statistically significant (Sirius TCP 4 mm: P = 0.24, Pentacam total corneal refractive power apex zone 4 mm: P = 0.64, Galilei TCP2: P = 0.24). Most of the manufacturer-provided measures did not correspond closely with the manifest refractive cylinder. When there were multiple measures of total corneal astigmatism, those derived from a zone with a diameter of 4.0 mm corresponded best with the manifest refractive cylinder. Conclusions: The CorT Total is a reliable benchmark measure that can be used to assess how well other measures of total corneal astigmatism correspond with the manifest refractive cylinder.